Beacon selection for localisation in IEEE 802.11 wireless infrastructure. (18th September 2013) - Kim, Ryangsoo; Lim, Hyuk; Jung, Daewon; Kim, Kapjin
Given the widespread deployment of IEEE 802.11–based access points (APs), received signal strength (RSS)–based localisation algorithms, which estimate the location of clients by measuring RSS at the installed APs, have drawn considerable attention. However, the accuracy of RSS–based localisation depends heavily on the RF and geometry characteristics between the client and the APs. In order to improve the localisation accuracy, the selection of an appropriate AP set without outliers is an important and challenging issue. In this paper, we first propose to use Cramér–Rao Bound, obtained from the average Fisher Information Matrix, as a criterion for selecting an appropriate AP set. Then, based on the proposed selection criterion, we develop a batch beacon selection algorithm that searches all the possible AP sets. Furthermore, to implement real–time mobile client localisation by alleviating computational complexity, we devise an online beacon selection algorithm.